Odpowiedź :
Odpowiedź:
2 a) 2*(-4)-1=-8-1=-9
7*5-1=35-1=34
7*0-1=0-1=-1
b) 6-3=3
6-(-2)=6+2=8
6-0=6
c) 5(9-5)=45-25=20
8(9-8)=72-64=8
-3(9-(-3))=-3(9+3)=27+9=36
d) 8-4*3=8-12=-4
8-4*(-3)=8+12=20
8-4*(1/4)= 8-1=7
a) x = -4 7 * (-4) - 1 = -29
x = 5 7 * 5 - 1 = 34
x = 0 7 * 0 - 1 = -1
b) x = 3 6 - 3 = 3
x = -2 6 + 2 = 8 (Jak byś nie zrozumiał to dlatego że dwa - dają +)
x = 0 6 - 0 = 6
c) x = 5 5(9 - 5) = 20
x = 8 8(9 - 8) = 8
x = (-3) -3(9 + 3) = -36
d) x = 3 8 - 4 * 3 = -4
x = -3 8 - 4 * -3 = 20
x = 0,25 8 - 4 * 0,25 = 7
Pozdro liczę na naj